Individual differences in physiologic measures are stable across repeated exposures to total sleep deprivation - Chua, Eric Chern‐Pin; Yeo, Sing‐Chen; Lee, Ivan Tian‐Guang; Tan, Luuan‐Chin; Lau, Pauline; Tan, Sara S.; Ho Mien, Ivan; Gooley, Joshua J. (Physiological reports, 2014)
Some individuals show severe cognitive impairment when sleep deprived, whereas others are able to maintain a high level of performance. Such differences are stable and trait‐like, but it is not clear whether these findings generalize to physiologic responses to sleep loss. Here, we analyzed individual differences in behavioral and physiologic measures in healthy ethnic‐Chinese male volunteers (n = 12; aged 22–30 years) who were kept awake for at least 26 h in a controlled laboratory environment on two separate occasions. Every 2 h, sustained attention performance was assessed using a 10‐min psychomotor vigilance task (PVT), and sleepiness was estimated objectively by determining percentage eyelid closure over the pupil over time (PERCLOS) and blink rate. Between‐subject differences in heart rate and its variability, and electroencephalogram (EEG) spectral power were also analyzed during each PVT. To assess stability of individual differences, intraclass correlation coefficients (ICC) were determined using variance components analysis. Consistent with previous work, individual differences in PVT performance were reproducible across study visits, as were baseline sleep measures prior to sleep deprivation. In addition, stable individual differences were observed during sleep deprivation for PERCLOS, blink rate, heart rate and its variability, and EEG spectral power in the alpha frequency band, even after adjusting for baseline differences in these measures (range, ICC = 0.67–0.91). These findings establish that changes in ocular, ECG, and EEG signals are highly reproducible across a night of sleep deprivation, hence raising the possibility that, similar to behavioral measures, physiologic responses to sleep loss are trait‐like. e12129 Individual differences in physiologic measures were examined in healthy ethnic‐Chinese males who underwent sleep deprivation in the laboratory on two different occasions. We found that between‐subject differences in ocular, electrocardiogram, and electroencephalogram measures were highly stable, even after adjusting for baseline individual differences in these measures. These results suggest that the brain responds predictably to the challenge of sleep deprivation and raise the possibility that physiologic responses to sleep loss are trait‐like.